1999
DOI: 10.1007/s000180050268
|View full text |Cite
|
Sign up to set email alerts
|

p53 in embryonic development: maintaining a fine balance

Abstract: In addition to its role as a tumour suppressor tenance of a fine balance of p53 protein levels within and cell-cycle checkpoint control protein, p53 has been embryonic cells is important for optimal development.Inappropriate overexpression or underexpression of p53 implicated as an important protein in embryonic development. Despite the viability of most p53 null mice, can lead to embryonic lethality or increased risk of evidence has accumulated that p53 may regulate differ-malformations. The p53 protein may u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
81
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(82 citation statements)
references
References 56 publications
1
81
0
Order By: Relevance
“…The function of p53 in development and its importance in the control of differentiation processes have been previously established with some discrepancies; some studies suggest that p53 facil-itates cell differentiation whereas in others it seems to be suppressive [51,52]. Our study showed that the expression of p53 protein in all cell types (SC, uMSC, dMSC, uASC and dASC) from the three different age donors did not differ significantly.…”
Section: Discussionmentioning
confidence: 42%
“…The function of p53 in development and its importance in the control of differentiation processes have been previously established with some discrepancies; some studies suggest that p53 facil-itates cell differentiation whereas in others it seems to be suppressive [51,52]. Our study showed that the expression of p53 protein in all cell types (SC, uMSC, dMSC, uASC and dASC) from the three different age donors did not differ significantly.…”
Section: Discussionmentioning
confidence: 42%
“…Because the G allele of SNP309 has a lower apoptotic frequency than the T allele in some cell types in culture (11,13), it is tempting to speculate that the presence of the G allele could compensate for higher apoptotic frequencies brought about by the p53-Arg isoform as populations move to northern Asia and Europe. A well regulated p53 pathway has been shown in many organisms to be crucial not only for tumor suppression but also for proper embryonic development (34,35); therefore, selection pressure on the p53 pathway could be possible. In fact, the p53 pathway also responds to inflammation, raising the possibility that infectious diseases could play a role in the selection of p53 pathway SNPs, like MDM2 SNP309 and codon 72.…”
Section: Discussionmentioning
confidence: 99%
“…These include cell cycle exit, which involves the activation of tumour suppressors p53 (Miller et al, 2003) and pRb (Slack et al, 1993;Slack et al, 1998). Both of them are important at various times of brain development (reviewed by Choi and Donehower, 1999), and their deficiency frequently results in brain anomalies (Armstrong et al, 1995) or embryonic death (Macleod et al, 1996;Slack et al, 1998). The role of pRb family members in terminal differentiation of neurons seems to be complex, as pRb has both cell cycle (cell-autonomous) and differentiation controlling functions (noncell-autonomous) (Liu et al, 2004).…”
Section: Introductionmentioning
confidence: 99%